Regenerative periodontal surgery in interproximal intrabony defects with biodegradable barriers - Dörfer, Christof; Kim, Ti-Sun; Steinbrenner, Harald; Holle, Rolf; Eickholz, Peter (Journal of clinical periodontology, 2000)
Aim: the comparison of the effects of guided-tissue regeneration (GTR) using 2 different biodegradable barriers (polylactide acetyltributyl citrate; polydioxanon) in 3- and 2-wall intrabony defects.